A Novel Indoline Derivative Ameliorates Diabesity-Induced Chronic Kidney Disease by Reducing Metabolic Abnormalities - Permyakova, Anna; Gammal, Asaad; Hinden, Liad; Weitman, Michal; Weinstock, Marta; Tam, Joseph (Frontiers in Endocrinology, 2020)
Both diabetes and obesity (diabesity) contribute significantly to the development of chronic kidney disease (CKD). In search of new remedies to reverse or arrest the progression of CKD, we examined the therapeutic potential of a novel compound, AN1284, in a mouse models of CKD induced by type-2 diabetes with obesity. Six week-old BKS Cg-Dock 7m+/+ Leprdb/J mice with type 2 diabetes and obesity were treated with AN1284 (2.5 or 5 mg.kg-1 per day) via micro-osmotic pumps implanted subcutaneously for 3 months. Measures included renal, pancreatic, and liver assessment as well as energy utilization. AN1284 improved kidney function in BSK-db/db animals by reducing albumin and creatinine and preventing renal inflammation and morphological changes. The treatment was associated with weight loss, decreased body fat mass, increased utilization of body fat toward energy, preservation of insulin sensitivity and pancreatic β cell mass and reduction of dyslipidemia, hepatic steatosis and liver injury. This indoline derivative protected the kidney from the deleterious effects of hyperglycemia by ameliorating the metabolic abnormalities of diabetes. It could have therapeutic potential for preventing CKD in human subjects with diabesity.